Development of the Convective Boundary Layer Capping with a Thick Neutral Layer in Badanjilin： Observations and Simulations - 韩博 吕世华 奥银焕 (Advances in atmospheric sciences, 2012)
In this study, the development of a convective boundary layer （CBL） in the Badaujilin region was investigated by comparing the observation data of two cases. A deep neutral layer capped a CBL that occurred on 30 August 2009. This case was divided into five sublayers from the surface to higher atmospheric elevations： surface layer, mixed layer, inversion layer, neutral layer, and sub-inversion layer. The development process of the CBL was divided into three stages： S1, S2, and S3. This case was quite different from the development of the three-layer CBL observed on 31 August 2009 because the mixed layer of the five-layer CBL （CBL5） eroded the neutral layer during S2. The specific initial structure of the CBL5 was correlated to the synoptic background of atmosphere during nighttime. The three-stage development process of the CBL5 was confirmed by six simulations using National Center for Atmospheric Research （USA） large-eddy simulation （NCAR-LES）, and some of its characteristics are presented in detail.